2018
DOI: 10.1002/chem.201800356
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Structure–Reactivity Correlations of Phenothiazine‐Based Fluorescent Probes toward ClO

Abstract: In this work, with the aim of developing effective molecular probes and investigating the structure-reactivity correlation, a short series of phenothiazine-based fluorescent probes are designed for the detection of ClO with differing electron push-pull groups. Sensing experiment results and single-crystal X-ray analysis with the aid of time-dependent DFT (TD-DFT) calculations reveal that substituting groups with increasing electron-withdrawing ability can increase the dihedral angle of the phenothiazine moiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It is worth noting that phenothiazine (PTZ)-based fluorescent probes usually have the advantages of high selectivity, good sensitivity, and short response time. [27][28][29][30][31][32] However, the emission wavelengths of PTZ itself and its derivatives are commonly too short to meet the in vivo imaging requirement. Thus, immense efforts have been paid to red-shift the emission wavelength to the visible or near-infrared region via a hybridization molecular engineering strategy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that phenothiazine (PTZ)-based fluorescent probes usually have the advantages of high selectivity, good sensitivity, and short response time. [27][28][29][30][31][32] However, the emission wavelengths of PTZ itself and its derivatives are commonly too short to meet the in vivo imaging requirement. Thus, immense efforts have been paid to red-shift the emission wavelength to the visible or near-infrared region via a hybridization molecular engineering strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, immense efforts have been paid to red-shift the emission wavelength to the visible or near-infrared region via a hybridization molecular engineering strategy. 27,29,[31][32][33] For example, Gupta et al reported an OCl − probe HCP with an emission maximum (λ em ) at 615 nm by conjugating PTZ with BODIPY through an ethylene group; 33 27,31,32 It should be noted that these hybridized probes usually display very weak fluorescence due to the intrinsic strong charge transfer (CT) nature. After oxidation of the sulfur atom to sulfoxide by hypochlorite, the charge transfer effect from the PTZ unit to the electron-withdrawing group could be inhibited, resulting in a turn-on fluorescence response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N and S atoms in PT molecule can endow PT with superior electron-donating ability, while the thioether can be specifically oxidized into the electron-withdrawing unit, sulfoxide structure, by ClO – . This strong contrast in electron-donating/-withdrawing property of PT molecule before and after being oxidized by ClO – can greatly tune the ICT and FRET processes within polymers, and this has been confirmed in the design of small-molecule fluorescent probes. , Consequently, the multicolored all-in-one polymers-derived Pdots-based probes can be achieved through adjusting ICT and FRET processes with the oxidation reaction between PT and ClO – . Combining the above design strategies (Scheme a), the design ideas of desired all-in-one fluorene-based polymers are described step by step from the perspective of fluorescence emission wavelength and signal output mode.…”
Section: Resultsmentioning
confidence: 99%
“…19 Thus, in such a context, we successfully synthesized the phenothiazine-thiophene acetonitrile compound PTZ-SCN through a simple Knoevenagel condensation reaction. 20,21 The newly synthesized PTZ-SCN demonstrated sensitivity and selectivity towards Cu 2+ in both simulated physiological conditions (CH 3 CN : HEPES buffer) and within cells. PTZ-SCN and PTZ-SCN-Cu 2+ were examined by various techniques.…”
Section: Introductionmentioning
confidence: 99%